2021
DOI: 10.1590/1678-4324-2021200802
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Effect on Bone Metabolism in Rats: a Systematic Review

Abstract: Caffeine is a highly-consumed substance around the world and can be found in various food sources and certain medications. The present systematic review aimed to evaluate the effect of caffeine on bone metabolism in rats. A systematic review was conducted in the PubMed, Medline, Scopus, Cocharane, Embase, and Clinical Trials.gov databases, and the Guidelines for Preferential Reporting for Systematic Reviews and Meta-Analyzes (PRISMA) were followed. In vivo experimental studies that presented caffeine as the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(72 reference statements)
0
0
0
Order By: Relevance
“…A systematic review showed both effects, caffeine can negatively interfere with bone metabolism by accelerating bone loss and delaying bone repair, or positive effect by activating osteogenesis and bone neoformation. [ 47 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review showed both effects, caffeine can negatively interfere with bone metabolism by accelerating bone loss and delaying bone repair, or positive effect by activating osteogenesis and bone neoformation. [ 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review showed both effects, caffeine can negatively interfere with bone metabolism by accelerating bone loss and delaying bone repair, or positive effect by activating osteogenesis and bone neoformation. [47] According to recommendations, caffeine intake should be below 400 mg/day [48] because a negative association between caffeine (>200-300 mg/day=~400-500 mL of coffee) and BMD has been reported, an effect which was attenuated with Ca intake >750 mg/day. [38,43] Consequently, the caffeine concentration found in our study (800 mg/L; 95% confidence interval, 610-860) for an estimated intake of 1 liter of YM per day would be above the daily recommendation.…”
Section: Discussionmentioning
confidence: 99%